Barriers of Reverse Logistics Implementation: A Case Study in a Car Battery Industry in Indonesia - Diana Puspita Sari; M. Mujiya Ulkhaq; Dyah Ika Rinawati; Dyah R. Rasyida (International Journal of Supply Chain Management, 2018)
There is a kindly new concept in logistics that related to the reusing, remanufacturing, and refurbishing of products, announced as reverse logistic (RL). While conventional or forward logistics is defined as the process of moving goods from the point of origin to the point of consumption, RL is defined contrarily. It allows the return of the products to be recycled, reworked, reused, or crushed for disposal. It has been growing out worldwide, affecting all the levels of supply chains in various industry sectors since the best RL operations would lead to higher sales revenue and reduced costs. However, regardless of its benefits, there are some barriers of the RL implementation, especially in the developing countries. The objective of this research is to identify the barriers of RL implementation in a car battery industry in Indonesia and study the interaction among those barriers to find the the root barrier using interpretative structural modelling. These barriers are then further analyzed using MICMAC analysis to look for the priority of the strategy to manage the barriers. The finding could help the managers to generate some policies toward the RL implementation.